Effectiveness of learning transfer in National Dual Training System (NDTS) - Ahmad, Azmi (2011)
Learning transfer is the ultimate goal of any training programme. The new Malaysian skills training is based on the dual learning principle in which trainees alternate between attending theoretical classes in the skills training institute and receiving onthe-job training at worksite. This new paradigm of skills training is better known as National Dual Training System (NDTS). The main problem is that there were complaints from the employers that the competencies of the output of the skills training in Malaysia are of poor quality. This was due to low absorption of learning transfer performance from training places to workplace. Apart from that there were little studies related to the effectiveness of learning transfer due to there is no acceptable way and mean to measure the learning transfer. The aim of this study was to ascertain on whether the effectiveness of learning transfer did occurred in the automotive mechatronics of NDTS programme. The research focus area is the Mechatronics Automotive course. A longitudinal study method was employed as the research methodology. The participants of this research were the trainees and coaches from NDTS Mechatronics Automotive course. The study utilised the selfadministered questionnaire, semi-structured interview, focus group and case study. Measuring 16 factors of the Learning Transfer System Inventory (LTSI) plus 3 factors derived from literature review and expert group discussion enable the researcher to determine the relationship between the learning transfer factors. It was found that NDTS training programme appears to have facilitated the positive transfer and near transfer from training situation to workplace environment. The findings of multiple regressions result suggest that the predictive variables explained 43.9% variance that has significance effect on the effectiveness of learning transfer. Apparently, the most influential dimensions of the effectiveness of learning transfer in NDTS were revealed as the course content, training delivery and working tasks. Interestingly, result indicated that the effectiveness of learning transfer in NDTS had occurred by the overall framework accuracy percentage of 79.2%. Therefore, the emerging effectiveness of learning transfer framework of NDTS in Malaysia is proposed